COMPUTER VIROLOGY: SELF-DEFENSE SYSTEM - Hamid M. A. Abdul-Hussain; Hamed Mizher Shabib (Journal of Engineering, 2007)
Based on the biological human models in defending human body against viruses, a new approach in designing the anti-virus system is introduced. This approach is called SDS( Self- Defence System). The principle of the SDS is that each executable program is responsible of defending itself against viral-attacks. In this system, each executable program is injected with basic anti-virus component which is called Self-Defence Routine. This routine, together with dedicated anti-virus loading program are used to construct the SDS which protects the computer system from virus invasion